2017
DOI: 10.1186/s12284-017-0174-1
|View full text |Cite
|
Sign up to set email alerts
|

Updating the elite rice variety Kongyu 131 by improving the Gn1a locus

Abstract: BackgroundKongyu 131 is an elite japonica rice variety of Heilongjiang Province, China. It has the characteristics of early maturity, superior quality, high yield, cold tolerance and wide adaptability. However, there is potential to improve the yield of Kongyu 131 because of the relatively few grains per panicle compared with other varieties. Hence, we rebuilt the genome of Kongyu 131 by replacing the GRAIN NUMBER1a (Gn1a) locus with a high-yielding allele from a big panicle indica rice variety, GKBR. High-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…In previous reports, the Gn1a Habataki (type 3) allele significantly increased GNPP by 21% and 28~37% in temperate japonica cultivar (Koshihikari and Sasanishiki) backgrounds, respectively 13 , 15 . In addition, the Gn1a -indica allele increased grain yield in Kongyu 131 27 with elite japonica background. However, in our study, the Gn1a -type 3 allele derived from lines Habataki, ST12, and ST6 was not effective in several indica cultivar backgrounds that had the Gn1a -type 2 allele.…”
Section: Discussionmentioning
confidence: 97%
“…In previous reports, the Gn1a Habataki (type 3) allele significantly increased GNPP by 21% and 28~37% in temperate japonica cultivar (Koshihikari and Sasanishiki) backgrounds, respectively 13 , 15 . In addition, the Gn1a -indica allele increased grain yield in Kongyu 131 27 with elite japonica background. However, in our study, the Gn1a -type 3 allele derived from lines Habataki, ST12, and ST6 was not effective in several indica cultivar backgrounds that had the Gn1a -type 2 allele.…”
Section: Discussionmentioning
confidence: 97%
“…However, limited research has been focused on the MAS of yield-related traits in recent decades. Recently, beneficial alleles of the GS3 , Gn1a , and Hd1 genes were introgressed into Kongyu131, a high-quality cultivar widely planted in the northeastern region of China, which improved both the grain yield and regional adaptation of the newly developed lines (Feng et al 2017 ; Nan et al 2018 ; Wang et al 2019 ). To date, many gene-linked markers have been developed to facilitate MAS breeding but these gene-linked markers are not associated with the target alleles for the genes and can only be used for allele mining after their association with the target allele is confirmed (Hu et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction, PCR and high-resolution melting (HRM) analysis were carried out as described by Feng et al [14]. According to the physical position of the cloned blast resistance genes and the SNPs between Kongyu-131 and GKGH, 12 SNP markers tightly linked to corresponding blast resistance genes were developed to genotype the F 2 population.…”
Section: Methodsmentioning
confidence: 99%
“…By resequencing the genome of Kongyu-131 and comparing it with cloned R-gene sequences, Zhang et al found that Kongyu-131 lacked almost all the R-genes except for Pish [13]. By using the principle of genome updating described by Feng et al [14], we mined a favorable blast resistance gene module (a small chromosome segment hosting a superior pi21 allelic variant from a blast-resistant upland variety) to improve the blast resistance of Kongyu-131 in this study.…”
Section: Introductionmentioning
confidence: 99%